2023
DOI: 10.3389/fpsyg.2022.922275
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability pedagogy: Understanding, exploring and internalizing nature’s complexity and coherence

Abstract: Online learning during the COVID-19 pandemic has affected student academic performance as well as mental, physical, and social wellbeing. During a lockdown at the University of Toronto in Canada (September 2020–April 2021), my students expressed an underlying sense of monotony yet uncertainty. I recalled a contrasting paradox from the teachings of Indigenous Cree on mental wellness in land-based experiences: a sense of stimulation and security that we can liken to variations of Appleton’s prospect-refuge theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…Spiegelaar recently found that a sustainability pedagogy approach that encouraged university students to connect with a sit spot every week and write reflections based on the experience and class readings supported student coping, comprehension, and sustainability mindsets during the COVID pandemic lockdown [20]. Additional research to support these findings may help to shift university pedagogies towards embodied experiences that facilitate healing and learning [20]. Evidence also suggests a need for more mixed-methods studies on student learning outcomes in higher education [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Spiegelaar recently found that a sustainability pedagogy approach that encouraged university students to connect with a sit spot every week and write reflections based on the experience and class readings supported student coping, comprehension, and sustainability mindsets during the COVID pandemic lockdown [20]. Additional research to support these findings may help to shift university pedagogies towards embodied experiences that facilitate healing and learning [20]. Evidence also suggests a need for more mixed-methods studies on student learning outcomes in higher education [21][22][23].…”
Section: Introductionmentioning
confidence: 99%